Measuring the use of human resources practices and employee attitudes: The linked personnel panel - Patrick Kampkötter; Jens Mohrenweiser; Dirk Sliwka; Susanne Steffes; Stefanie Wolter (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper introduces a new data source available for HRM researchers and personnel economists,the Linked Personnel Panel (LPP). The LPP is a longitudinal and representative employer-employee data set covering establishments in Germany and designed for quantitative empirical HR research. The LPP offers a unique structure. First, the data set combines employer and employee surveys that can be matched to each other. Second, it can also be linked to a number of additional administrative data sets. Third, the LPP covers a wide range of firms and workers from different backgrounds. Finally, because of its longitudinal dimension, the LPP should facilitate the study of causal effects of HR practices. The LPP employee survey uses a number of established scales to measure job characteristics and job perceptions, personal characteristics, employee attitudes towards the organisation and employee behaviour. This paper gives an overview of both the employer and employee survey and outlines the definitions, origins and statistical properties of the scales used in the individual questionnaire.
urn:nbn:de:bsz:180-madoc-401316
Keywords: 330; HR practices; matched employer-employee data; Linked Personnel Panel; employee attitudes